Relevance of the Principle of Publicity in Land Registration to the Protection of Civil Rights - Dian Dewi Khasanah; Tudi Iskandar (UNISSULA, 2026)
The principle of publicity in Indonesian land registration ensures legal certainty and civil rights protection by requiring land rights to be publicly recorded, making them legally binding on third parties. This article aims to analyze the position and meaning of the principle of publicity in the Indonesian land registration system, examine its implementation in land registration practices, and assess its role in the protection of civil rights and the resolution of land disputes. This study uses a qualitative design with a juridical normative approach through an analysis of the Basic Agrarian Law, Government Regulations on Land Registration, and current land policies, including the Complete Systematic Land Registration and the digitalization of land services. The results show that the principle of publicity plays a central role in creating legal certainty, protecting parties in good faith, and strengthening the proof of rights in civil land disputes. However, the dynamics of regulation and the acceleration of land registration require strengthening mechanisms for data transparency and accuracy so that the principle of publicity continues to function optimally. This research contributes theoretically to strengthening the doctrine of property law and practically provides recommendations for developing equitable land registration policies.